2021
DOI: 10.1002/jsfa.11673
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal digestion and absorption characterization in vitro of zinc‐chelating hydrolysate from scallop adductor (Patinopecten yessoensis)

Abstract: BACKGROUD: Zinc (Zn) is an essential catalytic element in the human health system but its absorption in the intestinal system can be strongly affected by gastrointestinal (GI) digestion. In this study, the food-derived potential Zn carrier, scallop adductor hydrolysates (SAHs), was produced and characterized. RESULTS: During temporary storage at 4 °C, SAH decreased in Zn-chelating capacity in the aqueous phase, whereas the SAH-Zn complex exhibited high stability. Moreover, the secondary structure of SAH had no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Based on the results, the existence of signals of zinc was clearly detected from the SMH‐Zn complex, suggesting that zinc successfully chelated SMH. Compared with our previous results, we also used elemental signatures tests of SEM to scan both food‐derived hydrolysates and synthetic peptides and the consistent results were obtained, reflected by similar contents of zinc (2.83% (Sun et al ., 2021a) and 6.88% (Wang et al ., 2022)). Therefore, in zinc‐chelated sea food‐derived hydrolysates or peptides, the proportion of zinc content might be no more than 10%, meaning the molecular ratio of peptides and zinc during chelation might be no more than 1:2 that was consistent with our previous results (Liu et al ., 2019a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results, the existence of signals of zinc was clearly detected from the SMH‐Zn complex, suggesting that zinc successfully chelated SMH. Compared with our previous results, we also used elemental signatures tests of SEM to scan both food‐derived hydrolysates and synthetic peptides and the consistent results were obtained, reflected by similar contents of zinc (2.83% (Sun et al ., 2021a) and 6.88% (Wang et al ., 2022)). Therefore, in zinc‐chelated sea food‐derived hydrolysates or peptides, the proportion of zinc content might be no more than 10%, meaning the molecular ratio of peptides and zinc during chelation might be no more than 1:2 that was consistent with our previous results (Liu et al ., 2019a).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we chose two groups of temperature (30–90 °C) and incubation time (10–50 min) into consideration of selection. Based on our results, we found that incubation temperature was not significantly involved in influencing the zinc‐chelating ability as well as our previous study (Sun et al ., 2021a) even though the other reposts discovered that proper heat would provide the energy (Sun et al ., 2021c) and improved the chelation between food‐derived peptides and metal (Zhang et al ., 2021). On the other hand, we also discovered that SMH could maintain relatively high zinc‐chelating ability in the high temperature of 80–90 °C with impressive heat stability.…”
Section: Resultsmentioning
confidence: 99%
“…Digestion and absorption are essential processes to maintain the life activities of organisms [ 74 ]. Disorder of this process will significantly reduce the efficiency of energy acquisition and inhibit the absorption and transport of nutrients [ 75 , 76 ]. In this study, protein digestion and absorption signaling pathway and carbohydrate digestion and absorption signaling pathway were enriched, and most DEGs enriched in pathways were down-regulated.…”
Section: Discussionmentioning
confidence: 99%